Urinary diseases and ethnobotany among pastoral nomads in the Middle East - Abu-Rabia Aref (BMC, 2005)
Abstract This article is derived from a broad, twenty-year study of ethnobotany and folk medicine among pastoral nomads in the Middle East which took place from 1984 to 2004. The article presents examples of different treatments of diseases and disorders of the urinary tract carried out by healer herbalists. The preparation of remedies includes boiling infusions, extraction of dry or fresh leaves, flowers, seeds or whole plants. Some of these plants were used both as food and as medicine, by ingesting different parts of the plants, such as leaves, flowers, fruits, and so on, either while soft, cooked or dried. Data were collected by using unstructured interviews and by observation. These plants were identified by healers, patients, and university botanists. This paper identified eighty-five plant species, which belong to thirty-six families. The most representative families are: Asteraceae (8), Brassicaceae (6), Poaceae (6), Umbelliferae (6).